2013
DOI: 10.1016/j.jhazmat.2013.04.048
|View full text |Cite
|
Sign up to set email alerts
|

Solidification/stabilization of toxic metals in calcium aluminate cement matrices

Abstract: The ability of calcium aluminate cement (CAC) to encapsulate toxic metals (Pb, Zn and Cu) was assessed under two curing conditions. Changes in the consistency and in the setting time were found upon the addition of the nitrates of the target metals. Both Pb and Cu caused a delay in CAC hydration, while Zn accelerated the stiffening of the mortar. Compressive strengths of the metal-doped mortars, when initially cured at 60ºC/100% RH, were comparable with that of the free-metal mortar. Three different pore size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(36 citation statements)
references
References 47 publications
4
31
1
Order By: Relevance
“…Both salts shortened the induction period: ZnCl 2 slightly reduced the induction period in comparison with the control sample resulting in a t max , time of the maximum of the heat release peak, of 7.16 h (7.65 for the control sample), whereas Zn(NO 3 ) 2 gave rise to a more intense reduction, t max = 3.64 h. It can be thus concluded that zinc chloride as well as zinc nitrate acted as accelerators when added to CA samples, shortening the induction period. This finding is in line with results published by Berger et al [17] for calcium sulfoaluminate cement and by our group for calcium aluminate cements [2], in which Zn(NO 3 ) 2 was seen to shorten the setting time of these cementitious materials. Another agreement can be mentioned regarding the moderate level of hydration that was observed for CA and CA 2 : this fact matches the XRD analysis of CAC with Zn(NO 3 ) 2 published in [2], and would explain the moderate decrease in compressive strengths observed for these samples when compared with plain samples.…”
Section: Zinc Saltssupporting
confidence: 93%
See 4 more Smart Citations
“…Both salts shortened the induction period: ZnCl 2 slightly reduced the induction period in comparison with the control sample resulting in a t max , time of the maximum of the heat release peak, of 7.16 h (7.65 for the control sample), whereas Zn(NO 3 ) 2 gave rise to a more intense reduction, t max = 3.64 h. It can be thus concluded that zinc chloride as well as zinc nitrate acted as accelerators when added to CA samples, shortening the induction period. This finding is in line with results published by Berger et al [17] for calcium sulfoaluminate cement and by our group for calcium aluminate cements [2], in which Zn(NO 3 ) 2 was seen to shorten the setting time of these cementitious materials. Another agreement can be mentioned regarding the moderate level of hydration that was observed for CA and CA 2 : this fact matches the XRD analysis of CAC with Zn(NO 3 ) 2 published in [2], and would explain the moderate decrease in compressive strengths observed for these samples when compared with plain samples.…”
Section: Zinc Saltssupporting
confidence: 93%
“…This finding is in line with results published by Berger et al [17] for calcium sulfoaluminate cement and by our group for calcium aluminate cements [2], in which Zn(NO 3 ) 2 was seen to shorten the setting time of these cementitious materials. Another agreement can be mentioned regarding the moderate level of hydration that was observed for CA and CA 2 : this fact matches the XRD analysis of CAC with Zn(NO 3 ) 2 published in [2], and would explain the moderate decrease in compressive strengths observed for these samples when compared with plain samples.…”
Section: Zinc Saltssupporting
confidence: 93%
See 3 more Smart Citations